A neutral polysaccharide from Ophiocordyceps lanpingensis restrains cisplatin‐induced nephrotoxicity. Issue 7 (11th May 2021) - Zhou, Shubo; Zhou, Yongchun; Yu, Jiaji; Jiang, Li; Xiang, Yingying; Wang, Juan; Du, Yaxi; Cui, Xiuming; Ge, Feng
Abstract: Ophiocordyceps lanpingensis is an edible mushroom distributed over the south‐eastern part of the Tibet Plateau, which is also recognized as an effective ethnomedicine to alleviate diseases. This study explored the effects of a kind of Ophiocordyceps lanpingensis neutral polysaccharide (ONP) on RAW264.7 macrophages and cisplatin‐induced nephrotoxicity. The results showed that ONP relieved the inflammatory response of RAW264.7 macrophages by increasing the expression level of anti‐inflammatory factor IL‐10. Furthermore, ONP treatment significantly prolonged the survival of the mice treated by cisplatin through decelerating pathological progress and alleviating damaged functions of the kidneys. Compared with the cisplatin group, ONP reduced the oxidative stress of the renal cells and the expression levels of pro‐inflammatory factors. Apoptosis of renal cells was also weakened in the ONP treatment group. These findings indicated that ONP alleviated cisplatin nephrotoxicity mainly by inhibiting oxidative stress, inflammation, and apoptosis in the kidneys, underscoring the potential of ONP supplementation to alleviate the side effects of cisplatin chemotherapy. Abstract : In conclusion, this study revealed the protective effects of ONP on DDP‐induced renal toxicity. Our findings indicated that ONP attenuated DDP nephrotoxicity mainly by reducing oxidative stress, inflammation and apoptosis in the kidneys, underscoring the potential of ONP supplementation to improve DDP chemotherapy.